The Influence of Psychological Well Being and Servant Leadership Toward Combat Readiness of The 469th Paskhas Command Battalion Soldiers in Carrying Out the Operation Task - Handayani, Sri Hastuti; Widana, I Dewa Ketut Kerta; Samudro, Eko G.; Mayori, Ersha (Technium Social Sciences Journal, 2022)
The 469th Paskhas Command Battalion is one of the Indonesian Air Force units involved in the Operation Task. In carrying out these tasks, Yonko 469 Paskhas soldiers are required to always have high combat readiness. However, the combat readiness condition of these soldiers seems to be optimal because, in fact, there are still many problems related to the readiness of soldiers in carrying out assignments outside their homebase. These problems are influenced by several factors, both internal and external, including the condition of the psychological well-being of soldiers and how the leadership of the unit commander is. This study aims to analyze the effect of psychological well-being and servant leadership on the combat readiness of Yonko 469 Paskhas soldiers. The research method used is quantitative with multiple regression techniques. The number of research subjects was 126 respondents, who were selected using a proportionate stratified random sampling technique from a total population of 269 soldiers with the rank of officer, bintara, and tamtama. The Combat Readiness Scale, Psychological Well Being Scale, and Servant Leadership Scale were used to collect data using SPSS version 26. The results of the study prove that (1) psychological well-being has a significant effect on combat readiness, meaning that the higher the psychological well-being, the combat readiness soldiers are getting taller. (2) Servant leadership has a significant effect on combat readiness, meaning that the more optimal the leader in implementing servant leadership is, the higher the combat readiness level of soldiers will be. (3) Psychological well-being and servant leadership simultaneously have a significant effect on combat readiness, meaning that the higher the level of psychological well-being of soldiers accompanied by the optimal application of servant leadership from the leader, the higher the level of combat readiness of soldiers.